Pengembangan Pengetahuan Anggota Indonesian Logistik Community (ILC) Chapter Akademisi Melalui Sosialisasi Halal Logistik dan Dangerous Goods - Lis Lesmini; Dian Anom Baskoro; Agus Setiawan (Institut Transportasi dan Logistik Trisakti, 2021)
Knowledge of Halal Logistics and Dangerous Goods is a basic necessity for logistics students in the era of asean economic and globalization society. Human resources readiness becomes a basic requirement to be able to compete for students. The partner of this activity is Indonesian Logistic Community (ILC) Chapter Academic. The problem facing partners today is the lack of knowledge of members on Halal Logistics and Dangerous Goods. The purpose of this activity is; provide basic knowledge about Halal Logistics and Dangerous Goods in the world of transportation and logistics, considering the increasing volume of movement of dangerous goods and also public interest in halal logistics as part of the lifestyle so that the logistics community needs to have knowledge about both things. Participants of this activity are members of ILC Chapter Academics plus PKM Team and ITL Trisakti students who numbered 94 people. The activity time is February 23, 2021. Method of activity through the introduction of Halal logistics and handling of dangerous goods using training methods, question and answer and video playback. The result of this activity is increased knowledge about Halal logistics and handling of dangerous goods in the world of transportation and logistics.